Historical maps as a neglected issue in history education. Students and textbooks representations of territorial changes of Spain and Argentina - Parellada, Cristian; Rodríguez-Moneo, María; Carretero, Mario (Frontiers in Education, 2024)
In the last years, history education has become a highly developed field, which is receiving considerable attention not only from educators but also from historians, philosophers of history, and social scientists in general. In this vein, seminal empirical and theoretical papers have focused on how history is taught to students and what are the different abilities that should be developed with the end to critically understand historical processes. These abilities are related to key concepts in the field as historical thinking, historical consciousness and historical culture. The aim of this paper is to focus on a matter not much considered in any of these approaches. This is to say, "where" the historical processes occurred. Usually the "where" implies a specific territory that is under dispute. In this vein, territories and their transformation through different time periods are represented by historical maps reproduced in atlas and textbooks. But these representations could have several bias and also tend to provide a number of incomplete ideas among the students and citizens in general. In relation to this, it is necessary study not only the features of historical maps but, also, how students appropriate them. This appropriation could be influenced by an essentialist view of the nation through historical master narratives. This is what we have found in our initial empirical studies in Spain and Argentina. Additional empirical studies are needed to improve history education studies from the point of view of the development of historical thinking and historical consciousness taking into account how historical maps and territorial changes are represented by both students and textbooks.